The effect of motivational interviewing and/or cognitive behaviour therapy techniques on gestational weight gain - a systematic review and meta-analysis - Helen Nightingale; George Mnatzaganian; Leesa Hooker; Stephen Barrett; Michael Kingsley (BMC, 2023)
Abstract Background Women with gestational weight gain (GWG) that is below or above recommendations are at risk of adverse perinatal outcomes. Motivational interviewing and/or cognitive behaviour therapy have demonstrated efficacy in initiating and sustaining behaviour change, including weight control. The objective of this review was to investigate the effect of antenatal interventions that include components of motivational interviewing and/or cognitive behaviour therapy on gestational weight gain. Methods This review was designed and reported in accordance with guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Five electronic databases were systematically searched to March 2022. Randomised controlled trials evaluating interventions with identified components of motivational interviewing and/or cognitive behaviour therapies were included. Pooled proportions of appropriate GWG and GWG above or below guidelines, and standardised mean difference for total gestational weight gain, were calculated. Risk of bias in included studies was evaluated using the Risk of Bias 2 tool, and the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach was used to evaluate the quality of evidence. Results Twenty-one studies (8030 participants) were included. Overall, MI and/or CBT interventions had a small effect on the total gestational weight gain (SMD: -0.18, 95% confidence interval: -0.27 to -0.09, p < 0.001) and improved the proportion of women achieving recommended gestational weight gain (29% versus 23% in the comparison, p < 0.001). The GRADE assessment indicated that overall quality of evidence is very uncertain, however sensitivity analyses to account for high risk of bias produced similar results to original meta-analyses. The magnitude of effect was greater in women with overweight or obesity when compared to women with BMI < 25 kg/m2. Conclusion Motivational interviewing and/or cognitive behaviour therapy techniques may be effective for promoting healthy gestational weight gain. Nevertheless, a high proportion of women do not achieve recommended gestational weight gain. Future interventions should consider factors, including clinician and consumer perspectives, in the design and delivery of psychosocial interventions that aim to support healthy gestational weight gain. Trial registration The protocol for this review was registered with the PROSPERO International register of systematic reviews (registration number CRD42020156401).